2021
DOI: 10.3390/su13126935
|View full text |Cite
|
Sign up to set email alerts
|

An Item Response Theory to Analyze the Psychological Impacts of Rail-Transport Delay

Abstract: Questionnaire instruments have been used extensively by researchers in the literature review for evaluation of various aspects of public transportation. Important implications have been derived from those instruments to improve various aspects of the transport. However, it is important that instruments, which are designed to measure various stimuli, meet criteria of reliability to reflect a real impact of the stressors. Particularly, given the diverse range of commuter characteristics considered in this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The outcome measure is based on theta in IRT. In contrast, in CTT, the outcome measure is based on the sum of the score distribution [24].…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome measure is based on theta in IRT. In contrast, in CTT, the outcome measure is based on the sum of the score distribution [24].…”
Section: Problem Statementmentioning
confidence: 99%
“…Source: (Rezapour et al (2021) [24]). The probability of selecting the ith item is provided in Equation ( 2), θ m = (α i , β i ) is the ability or latent trait for individual m, α i is the discrimination parameter for item i, location of extremity boundary for item i defined as difficulty parameter is β i (if constrained can be considered constant for all items), and θ m is the ability of respondents m on various questions or items.…”
Section: Irtmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of instrument evaluation, the majority of past studies only employed the traditional Cronbach alpha method, and a single study employed the IRT in the field of transportation ( Rezapour et al, 2021 ). So a comprehensive application of MSA is missing from the past studies in the context of transport.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of evaluating instruments, the authors have only found a single study conducted with the help of IRT ( Rezapour et al, 2021 ) in the context of transportation, while no study has employed the MSA technique in the context of transport psychology. Implementation of the MSA is important due to the possible limitations of the IRT.…”
Section: Introductionmentioning
confidence: 99%